If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(3 + -1x) + 1 = 4(x + -1) + -3 (3 * -2 + -1x * -2) + 1 = 4(x + -1) + -3 (-6 + 2x) + 1 = 4(x + -1) + -3 Reorder the terms: -6 + 1 + 2x = 4(x + -1) + -3 Combine like terms: -6 + 1 = -5 -5 + 2x = 4(x + -1) + -3 Reorder the terms: -5 + 2x = 4(-1 + x) + -3 -5 + 2x = (-1 * 4 + x * 4) + -3 -5 + 2x = (-4 + 4x) + -3 Reorder the terms: -5 + 2x = -4 + -3 + 4x Combine like terms: -4 + -3 = -7 -5 + 2x = -7 + 4x Solving -5 + 2x = -7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -5 + 2x + -4x = -7 + 4x + -4x Combine like terms: 2x + -4x = -2x -5 + -2x = -7 + 4x + -4x Combine like terms: 4x + -4x = 0 -5 + -2x = -7 + 0 -5 + -2x = -7 Add '5' to each side of the equation. -5 + 5 + -2x = -7 + 5 Combine like terms: -5 + 5 = 0 0 + -2x = -7 + 5 -2x = -7 + 5 Combine like terms: -7 + 5 = -2 -2x = -2 Divide each side by '-2'. x = 1 Simplifying x = 1
| A=47.5+-0.5*9 | | 59+44t=19t-39 | | 3x+44=8x-6 | | 8y=3(y-5) | | 4x-5=9x-7 | | X^3-3x^2-104x+216=0 | | 2x+3=9x-7 | | 2(0)=3y-13 | | e^6x=55e^9x | | .59+.44t=1.9t-.39 | | 5c-4(c-9)=2+2c | | 5(-1)-2y=-19 | | 6r^2-9=-3r | | -(1-x)=2(4-x) | | 6x-22=8x-34 | | 0.6(x+-.0300)=0.65-0.01(x+1) | | 5*47.5+-0.5b+4b=269 | | 3m^2=12 | | 5y+2(4)=58 | | 3x+6=5+2x | | x=5x-45 | | 5h+4h+3= | | 9x-40+3x-30=180 | | 2(x^2+4)+5(x+2)-3=0 | | x+3=-1+2x | | x+13=19x | | -10+6y=25+y | | 6p^2-10=0 | | 9(-3)+5y=-33 | | 5-2(x+21)=12 | | 36-10m=2(m-2) | | 0=(5x+6)(x-9) |